Indonesian Business Polytechnic New Student Admissions Test Using a Computer Based Test (CBT) - Novendra Adisaputra Sinaga; Firinta Togatorop (Institute of Computer Science (IOCS), 2020)
New Student Admission Is One Process in Higher Education which aims to filter out prospective students who are selected according to the criteria determined by the Higher Education to become their students. In general, the process of admitting new students is carried out through the stages of registration, selection tests, and student admissions. Every year, Politeknik Bisnis Indonesia conducts the Entrance Examination for ± 300 people, which is done manually so it takes longer time to print the questions, check the results of the exam and report the results of the exam. Computer Based Test (CBT) by utilizing the Moodle CMS is one of the evaluation strategies used to determine the capacity and competence of prospective new students more quickly and more efficiently. Utilizing this application simplifies the work of the Exam Committee so that it is more productive and professional in managing Administration. This application also requires prospective students to be accustomed to using the application and must be more mature in carrying out the examination because it does not allow working with others because the questions and answer choices appear randomly.